Integrative genomics of gene and metabolic regulation by estrogen receptors α and β, and their coregulators. Issue 4 (25th April 2017) - Madak‐Erdogan, Zeynep; Charn, Tze‐Howe; Jiang, Yan; Liu, Edison T; Katzenellenbogen, John A; Katzenellenbogen, Benita S
Abstract :